(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2025)
The well-known manuscript Vat.lat.11257.pt.A, which is kept in the Vatican Library, contains a plan drawing of a single-nave church with side chapels that was drawn up by Francesco Incarnatini. He was a Roman painter active at the Savoy court. This paper aims to investigate the implications of this drawing.